Characterisation of the role of the Candida albicans Tor1 Pathway in regulating flocculation biofilm formation & hyphal growth - Flanagan, Peter Richard (Trinity College (Dublin, Ireland). School of Dental Science, 2016)
Candida species are responsible for a wide range of superficial and life threatening infections and are the fourth most common cause of nosocomial bloodstream infections. Candida albicans is an opportunistic pathogen that is a commensal inhabitant of the alimentary canal. The ability to adapt to various nutritive environments presented by the host is essential to its survival as a commensal or pathogen. Thus, understanding how cell growth is controlled in response to environmental signals remains an active field of research. Target of rapamycin (Tor1) is a highly conserved protein kinase from mammalian to yeast cells. In eukaryotes, Tor is responsible for regulating metabolism and the cell cycle. In Saccharomyces cerevisiae, Tor is stimulated by amino acids and an active Tor kinase promotes ribosome biogenesis and glycolysis, as well as repressing genes involved in nitrogen scavenging. Current literature presents several lines of evidence indicating that in Candida spp., Tor may play a role in the transition of yeast-to-hyphae. This study aims to determine if the Tor1 fungal kinase is a central regulator of virulence by characterising the role of Tor1 and the putative upstream activators of Tor1.
Keywords: Dental Science, Ph.D.; PhD Trinity College Dublin, 2016